Persepsi Tradisi Tompangan Sebagai Bentuk Investasi Masyarakat Andulang Gapura Sumenep - Moch. Ramdany; Ahmad Majdi Tsabit (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
Perception of the tradition of bringing money and goods or souvenirs with the term Tompangan in Andulang Village. It is an individual or group behavior that gives and helps with a gesture of reciprocation with the proverb of tengka debt at a wedding ceremony in the Madurese language of the eastern region known as Ghabay. Could you bring money or goods written in the notebook and a receipt for detailed return information, receive it, and give support? This study aims to determine the public's perception of the traditional tompangan procession as a form of investment and an Islamic concept (Al adah Muhakkamah). This method uses a qualitative approach with ethnographic studies using data collection techniques in interviews, observation, and documentation. Meanwhile, the sampling technique involved 10 respondents as snowbell sampling from all village residents. As a result, people are encouraged to exchange money for goods with a unique attraction, and people are even tempted and have a dilemma. So, it contains a positive or negative side to the Tompangan tradition because individuals bear risks. When you receive a lift on the price of cheap goods, the opposite is also true when you return the price of expensive goods. The Tompangan tradition has a notary administration for the recipient of the Tompangan, while the form of investment is giving support, such as assistance or a debt of gratitude, which is a gesture in the hope of reciprocity, in the form of returning goods that are similar or can be cashed in at the value prevailing at the time of returning the Tompangan goods. Specifically, the community intends to carry out this tradition, whether from a sharia or muamalah investment perspective. Because it can be considered by those who give and receive, don't lose your book records and receipts.